SUMBER HUKUM ISLAM: KEDUDUKAN AL-QUR’AN SEBAGAI SUMBER HUKUM SYARA’ - Hopipah, Eva Nur; Syafe'i, Abdullah (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
ABSTRACT The first and foremost source of syara' law is the Al-Qur'an and the argument comes from revelation. The position of the Al-Qur'an as evidence is not in doubt because there are many arguments which prove that the Al-Qur'an is the main source of syara' law before using other sources of law. The authenticity of the Al-Qur'an is certainly not in doubt, until now, its authenticity is still maintained. Allah sent down the Qur'an, of course there is a function, benefit, or purpose behind it. As a guide, differentiator, explanation, grace, teaching, good news, light, a source of wisdom, to the Al-Qur'an as syifau al-shudur or medicine for spiritually sick. The Qur'an is of course the main source of fiqh law to provide benefit to humans. This paper uses the research library research method which is comprehensively discussed with the aim of being able to provide insight regarding the position of the Qur'an as a source of syara' law. Keywords: Source of Syara Law, Position of Al-Qur'an, Ushul Fiqh